Spatial Boundaries of the Rainwater Drainage Network and its Impact on Drainage Efficiency in the Urban Area of Misurata Municipality. (Journal of Libya for geographical studies, 2024)
In this research, the researchers seek to reveal the map of the rainwater drainage network, as well as the percent of its coverage of the entire urban zone in Misurata municipality, inventory the component of the drainage system, evaluate the efficiency of water drainage process during rain full, identifying the existing deficiencies, list the problems and difficulties that affect the level of efficiency of the system's work and finally knowing the available alternatives for draining the rainwater from the streets in the study area.The research was divided into four sections, the first section dealt with theoretical framework of the study, the second section introduced a general overview of the geographical characteristics of the urban area in Misurata municipality, while the third was devoted to study the spatial boundaries of the existing rainwater drainage system. Finally, in the fourth section, the expansion projects and development of the rainwater drainage system and the alternatives outside the scope of  the network were investigated. For collecting the data related to the research topic, a questionnaire and interviews with specialists were used, as well as, to display the data, we used tables, cartography ( using ArcMap 10.5 software) and photographs.  The research ended up with a sets of results; the rainwater drainage network – the current situation- was implemented in two phases, the first, in the period ( 1967- 1972), while the second, in the period ( 1982- 1992) and the spatial boundaries of the network form the a circular zone around the city center, includes the urban zone within the third ring road, and the limited zones between the third and fourth ring road, with a general percentage not exceeding 9.20% of the total urban zone in the study area, and the existing rainwater drainage system is mostly old, and suffers from a number of technical problems that affect its level of efficiency.
Keywords: Rainwater Drainage System; Drain sink; Collecting and Pumping Stations; Existing Situation; Integrated Facilities